Contrastive and Error Analysis of Indonesian Learners’ Tense and Aspect Usage in English Writing - Siti Ismahani; Sofiyani Nasution; Rizky Ummi Thahira Nasution; Indah Permatasari Harahap; Gairah Riski Harahap (Jurnal Pendidikan dan Sastra Inggris, 2024)
This study investigates Indonesian learners’ use of English tense and aspect by employing an integrated framework that combines contrastive analysis and error analysis. A total of sixty short essays written by university-level EFL students were analyzed to identify recurring patterns of tense–aspect errors and to uncover the linguistic and cognitive sources behind them. The findings reveal three dominant error types—misformation, omission, and overgeneralization which reflect both negative transfer from Indonesian and developmental characteristics of learners’ interlanguage. Learners frequently produced incorrect verb forms, omitted obligatory auxiliaries, and applied tense rules inconsistently, particularly when attempting to construct more complex narrative sequences. Among all structures examined, the present perfect tense emerged as the most challenging, largely because Indonesian lacks an equivalent grammatical form, resulting in persistent confusion in mapping English verb forms to temporal and aspectual meanings. The study also found that students often relied on surface-level rules rather than deeper semantic understanding, which contributed to inaccurate tense selection across contexts. These results underscore the need for contextualized, awareness-raising instruction that encourages learners to connect form, meaning, and use more systematically. Overall, the study demonstrates the pedagogical significance of integrating contrastive and error analysis to enhance learners’ accuracy and competence in academic English writing.